2010 IEEE International Conference on Systems, Man and Cybernetics 2010
DOI: 10.1109/icsmc.2010.5642329
|View full text |Cite
|
Sign up to set email alerts
|

Voice pitch control using tactile feedback for the deafblind or the hearing impaired persons to assist their singing

Abstract: It is difficult for the deatblind or the hearing impaired to control their voice pitch because they cannot perceive it. In particular, when singing it is very difficult for them to control their voice pitch because they must maintain a stable tone.In this research, a voice pitch control system is developed to assist their singing by means of a tactile display. The tactile musical note display has 64 piezoelectric vibrators arranged in four rows (16 x 4 rows). A user rests the last joint of an index finger on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The interval deviation, which is the absolute difference without tactile feedback with tactile feedback between the target musical interval and the voice pitch of the subject, was calculated with reference to our previous study [5]. Figure 5 shows the mean interval deviations of pitch for each note for all subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interval deviation, which is the absolute difference without tactile feedback with tactile feedback between the target musical interval and the voice pitch of the subject, was calculated with reference to our previous study [5]. Figure 5 shows the mean interval deviations of pitch for each note for all subjects.…”
Section: Resultsmentioning
confidence: 99%
“…However, only a few studies have been made on presenting a musical scale using a tactile display, or on voice training to adjust musical interval using tactile feedback. In light of this, we have developed a voice pitch control system that uses a two-dimensional tactile display [5]. The results of our research showed that two deafblind subjects could control their voice pitch with as much accuracy as hearing children.…”
Section: Introductionmentioning
confidence: 99%
“…Sakajiri et al [21] developed a voice step control system with the aim of helping their songs via a touch screen for deaf in their studies.…”
Section: Related Workmentioning
confidence: 99%
“…The musical notation for "Tulip" is also shown in Figure 5. "Frog Round" was used in our previous study [5]. In "Frog Round," successive notes in the melody are adjacent notes in the scale.…”
Section: B Proceduresmentioning
confidence: 99%
“…Only a few studies have examined the presentation of a musical scale using a tactile display for voice training in adjusting musical intervals using tactile feedback. In light of this, we have developed a voice pitch control system that uses a two-dimensional tactile display [5]. The results of this research showed that two deafblind subjects could control their voice pitch with as much accuracy as hearing children while singing the song "Frog Round."…”
Section: Introductionmentioning
confidence: 99%